2023
DOI: 10.3390/pr11061765
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Hydrogen-Rich Syngas Production from Coal Gasification

Abstract: Coal gasification is recognized as the core technology of clean coal utilization that exhibits significant advantages in hydrogen-rich syngas production and CO2 emission reduction. This review briefly discusses the recent research progress on various coal gasification techniques, including conventional coal gasification (fixed bed, fluidized bed, and entrained bed gasification) and relatively new coal gasification (supercritical water gasification, plasma gasification, chemical-looping gasification, and decoup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 164 publications
0
5
0
Order By: Relevance
“…It can be seen clearly in Figure 10 that the solid particles in the high-speed bed enter the low-speed bed from the connecting hole in the upper part of the high-speed bed, while the solid particles in the low-speed bed enter the high-speed bed from the connecting hole in the lower part of the low-speed bed, which shows that the internal recycling is achieved between the two beds. Moreover, there are several flow vortexes formed in the beds, which can enhance mass transfer between the gas phase and the solid phase [44,45].…”
Section: Velocity Profiles Of Solid Phasementioning
confidence: 99%
“…It can be seen clearly in Figure 10 that the solid particles in the high-speed bed enter the low-speed bed from the connecting hole in the upper part of the high-speed bed, while the solid particles in the low-speed bed enter the high-speed bed from the connecting hole in the lower part of the low-speed bed, which shows that the internal recycling is achieved between the two beds. Moreover, there are several flow vortexes formed in the beds, which can enhance mass transfer between the gas phase and the solid phase [44,45].…”
Section: Velocity Profiles Of Solid Phasementioning
confidence: 99%
“…3 Several existing methods for hydrogen production, such as coal gasification, steam reforming, and water electrolysis, have been employed. 4 However, the utilization of electrocatalysts to stimulate the hydrogen evolution reaction (HER) has been identified as a particularly efficient methodology for prospective hydrogen production, primarily because of its low reaction environment requirement (room temperature), environmentally friendly hydrogen source (i.e., water), and easy separation of the products (hydrogen and oxygen are produced at different electrodes). 4,5 Electrocatalysts that exhibit high activity and low HER overpotential are crucial for enhancing the sluggish HER kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…In response to the pressing need to address the energy crisis and the severity of environmental issues, researchers have been actively engaged in the investigation of clean and sustainable energy resources that can substitute conventional fossil fuels. , Owing to its zero carbon emissions and considerable energy density, hydrogen is universally acknowledged as a promising new energy source poised to accommodate the escalating demand for energy . Several existing methods for hydrogen production, such as coal gasification, steam reforming, and water electrolysis, have been employed . However, the utilization of electrocatalysts to stimulate the hydrogen evolution reaction (HER) has been identified as a particularly efficient methodology for prospective hydrogen production, primarily because of its low reaction environment requirement (room temperature), environmentally friendly hydrogen source (i.e., water), and easy separation of the products (hydrogen and oxygen are produced at different electrodes). , Electrocatalysts that exhibit high activity and low HER overpotential are crucial for enhancing the sluggish HER kinetics .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term production practices in the coal chemical industries have demonstrated that coal gasification is pivotal for improving economic efficiency and reducing environmental pollution. On the other hand, most current coal gasification processes yield syngas with relatively low effective gas content (Hydrogen, H 2 and Carbon monoxide, CO), especially the H 2 content [3][4][5][6]. For example, Lurgi and British Gas Lurgi are two representative commercialized coal gasification technologies.…”
Section: Introductionmentioning
confidence: 99%